2004
DOI: 10.1111/j.1365-2044.2004.03943.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bupropion as an aid to stopping smoking before elective surgery: a randomised controlled trial

Abstract: SummarySmoking is a risk factor for complications during and after surgery, but most smokers are unable to quit before elective surgery. We tested the efficacy of bupropion in improving smoking cessation rates in this setting by enrolling 47 patients from the elective surgery waiting list in a double-blind randomised controlled trial. Patients receiving bupropion had a lower daily cigarette consumption at the time of hospital admission, median (IQR) cigarettes per day: 6 (2-7) vs. 15 (9-20), p = 0.046. They al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 29 publications
1
67
2
2
Order By: Relevance
“…21 None of the trials reported complete follow-up with the highest rate of dropout reported in Myles' study (42%). 15 This study showed that study compliance was higher in the active treatment group, indicating that dropout from the study generally followed an unsuccessful quitting attempt. However, this finding was not found in the other included trials where the drop-out rate ranged between 14-15%.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…21 None of the trials reported complete follow-up with the highest rate of dropout reported in Myles' study (42%). 15 This study showed that study compliance was higher in the active treatment group, indicating that dropout from the study generally followed an unsuccessful quitting attempt. However, this finding was not found in the other included trials where the drop-out rate ranged between 14-15%.…”
Section: Discussionmentioning
confidence: 86%
“…Two double-blind, placebo-controlled trials 15,17 studied the efficacy of counseling and pharmacotherapy (bupropion or NRT) vs usual care and placebo. However, two trials 16,18 examined the effect of more intensive behavioural interventions (e.g., a computer-assisted counseling program or counseling sessions followed by postoperative telephone follow-up) and NRT in promoting smoking cessation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…= non significant; sig. = statistically significant * = post-operatively abstinence or reduction by more than half or normal daily rate A number of different intervention methods were used in the papers: six studies used some form of counselling (McHugh et al, 2001;Moller, et al, 2002;Molyneux et al, 2003;Ratner et al, 2004;Sorensen, & Jorgensen, 2003;Wolfenden et al, 2005), five studies used counselling together with Nicotine Replacement Therapy (NRT) (Moller, et al, 2002;Molyneux et al, 2003;Ratner et al, 2004;Sorensen, & Jorgensen, 2003;Wolfenden et al, 2005), one study used only NRT (bupropion) (Myles et al, 2004), one study used a letter offering smoking cessation advice (Andrews et al, 2006), one study delivered smoking cessation advice via an audio cassette (Myles et al, 1996) and one study used counselling, NRT and offered self-help material tailored to individual needs (Wolfenden et al, 2005). Thus most interventions used a multifaceted behavioural approach.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Table 1 summarises the studies included in this review. Of the nine studies, three were conducted the UK, (Andrews et al, 2006;McHugh et al, 2001;Molyneux et al, 2003) three in Australia, (Myles et al, 1996;Myles et al, 2004;Wolfenden et al, 2005) two in Denmark (Moller, et al, 2002;Sorensen, & Jorgensen, Key: CABG = Coronary Artery Bypass Graft surgery; Exp = Experimental Group; Con = Control Group; n.s. = non significant; sig.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation